Development of Science Process Skills Assessment Instruments in Online Magnetic Field Lab Labs Using Remote Physics Labs - Rini Irmah; Ishafit Ishafit; Dian Artha K; Moh. Toifur (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to develop and test the feasibility of a science process skills (SPS) assessment instrument in an online magnetic field practicum on the topic of single coils using Remote Physics Lab (R-PhyLab). The study used the Research and Development (R&D) method with a 4D model (Define, Design, Develop, Disseminate) limited to the Develop stage. The instrument was structured in 15 multiple-choice questions covering five aspects of SPS: observing, predicting, measuring, interpreting data, and communicating scientifically. Content validation by three experts using the Gregory formula resulted in an 80% suitability level, with 12 items declared valid and 3 items requiring revision. The trial was conducted on two groups of students at MAN Insan Cendekia Paser. The analysis results showed that all questions were in the easy category (P > 0.70) and the instrument reliability was in the moderate category (KR-20 = 0.46). This instrument has implications for the availability of measuring tools that can help physics teachers identify students' scientific skills authentically in the context of online practicums. In the future, this instrument can be adapted for other physics topics or developed with a more varied assessment format to support deep learning-based learning in the understanding phase.